Calendar time‐specific propensity scores and comparative effectiveness research for stage III colon cancer chemotherapy1. (7th January 2013) - Mack, Christina DeFilippo; Glynn, Robert J.; Brookhart, M. Alan; Carpenter, William R.; Meyer, Anne Marie; Sandler, Robert S.; Stürmer‎, Til
ABSTRACT Purpose Nonexperimental studies of treatment effectiveness provide an important complement to randomized trials by including heterogeneous populations. Propensity scores (PSs) are common in these studies but may not adequately capture changes in channeling experienced by innovative treatments. We use calendar time‐specific (CTS) PSs to examine the effect of oxaliplatin during dissemination from off‐label to widespread use. Methods Stage III colon cancer patients aged 65+ years initiating chemotherapy between 2003 and 2006 were examined using cancer registry data linked with Medicare claims. Two PS approaches for receipt of oxaliplatin versus 5‐flourouricil were constructed using logistic models with key components of age, sex, substage, grade, census‐level income, and comorbidities: (i) a conventional, year‐adjusted PS and (ii) a CTS PS constructed and matched separately within 1‐year intervals, then combined. We compared PS‐matched hazard ratios (HRs) for mortality using Cox models. Results Oxaliplatin use increased significantly; 8% (n = 86) of patients received it in the first time period versus 52% (n = 386) in the last. Channeling by comorbidities, income, and age appeared to change over time. The CTS PS improved covariate balance within calendar time strata and yielded an attenuated estimated benefit of oxaliplatin (HR = 0.75) compared with the conventional PS (HR = 0.69). Conclusion In settings where prescribing patterns have changed and calendar time acts as a confounder, a CTS PS can characterize changes in treatment choices and estimating separate PSs within specific calendar time periods may result in enhanced confounding control. To increase validity of comparative effectiveness research, researchers should carefully consider drug lifecycles and effects of innovative treatment dissemination over time. Copyright © 2013 John Wiley & Sons, Ltd.